1973
DOI: 10.1111/j.1399-3054.1973.tb08581.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigations on the Nature of the Heat Resistance of Thermophilic Bacteria

Abstract: When cells of Bacillus stearothermophilus, strain NCA 1503, were grown in tryptone starch broth and subsequently transferred to tris buffer, a fraction of tbe celis: rapidly died in the buffer. This fraction increased with increasing content of calciiina chloride in the growth medium. The addition of sodiom, potassium or magnesium chloride to the growth medium had no such effect. The rapid dying of the cells in tris buffer "was associated with a leakage of organic material and calcium ions from the cells. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The Arrhenius plot in fig.4 indicates that the Thus calcium appears to be taken up by living calcium uptake rate increases with temperature, in cells at a rate which increases with temperature. In accordance with the higher demand for calcium at the light of earlier results [6,7] that calcium is needed for survival at high temperatures, we conclude that calcium is not just accumulated as a consequence of, but is indeed required for thermophilic growth of B. stearothermophilus.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The Arrhenius plot in fig.4 indicates that the Thus calcium appears to be taken up by living calcium uptake rate increases with temperature, in cells at a rate which increases with temperature. In accordance with the higher demand for calcium at the light of earlier results [6,7] that calcium is needed for survival at high temperatures, we conclude that calcium is not just accumulated as a consequence of, but is indeed required for thermophilic growth of B. stearothermophilus.…”
Section: Resultssupporting
confidence: 68%
“…In our view, calcium stabilizes the cell functions against the action of heat. The general validity of other theories attempting to explain why thermophilic bacteria are able to grow at high temperatures has been discussed by Ljunger [6,7], and this subject has been reviewed recently [8].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of determining the number of viable cells in a thermophilic culture by plating was first highlighted by Allen [1] who concluded that the method may be expected to give results which are too low because of death of some cells, viable at the time of sampling, before they can develop into colonies. Ljunger [2,3] confirmed that, when cells of Bacillus stearothermophilus grown in broth were transferred to a buffer, a fraction of the cells died rapidly and suggested that an active transport of calcium ions into the cell was needed for viability. Active transport of calcium by B. stearothermophilus was subsequently demonstrated by Stahl [4].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 96%
“…Ljunger [1,2] suggested that a high intracellular calcium concentration in cells of thermophilic bacteria is of fundamental importance for their heat stability. Cells of Bacillus stearothermophilus, which is an obligately thermophilic organism, rapidly die at 55°C unless the surrounding medium contains calcium, potassium, phosphate and an energy source [1 ].…”
Section: Introductionmentioning
confidence: 99%